2020
DOI: 10.1016/j.ipm.2019.102142
|View full text |Cite
|
Sign up to set email alerts
|

Graph neural news recommendation with long-term and short-term interest modeling

Abstract: With the information explosion of news articles, personalized news recommendation has become important for users to quickly find news that they are interested in. Existing methods on news recommendation mainly include collaborative filtering methods which rely on direct user-item interactions and content based methods which characterize the content of user reading history. Although these methods have achieved good performances, they still suffer from data sparse problem, since most of them fail to extensively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(68 citation statements)
references
References 27 publications
1
61
0
Order By: Relevance
“…e above observation has proved that aggregating the features of too many neighbors will increase the noise in the user's representation, which is described in Section 4.2. Other related studies have empirically found similar trends, with the best layer size set as L � 2 [32,38].…”
Section: Ablation Experimentssupporting
confidence: 60%
“…e above observation has proved that aggregating the features of too many neighbors will increase the noise in the user's representation, which is described in Section 4.2. Other related studies have empirically found similar trends, with the best layer size set as L � 2 [32,38].…”
Section: Ablation Experimentssupporting
confidence: 60%
“…erefore, the user preference changes need to be fully recognized to ensure the effectiveness of recommendations. Generally, the user preferences can be divided into long-term preferences and short-term preferences [18,19,22,23]. e former characterizes the user general interests that are relatively stable or that change slowly over time, whereas the latter usually refers to the user temporal interests, and they can be easily influenced by a variety of factors, such as user instant demands, recent interests, and global mainstream trends in a short period of time [18].…”
Section: User Preferences Changesmentioning
confidence: 99%
“…Recently, the user long-term and short-term preferences have drawn attention from research to obtain more precise and accurate user preference profiles and improve the recommendation performance [18,22,23,45]. For example, Tan and Liu [22] incorporated an attention mechanism into a recurrent neural network to capture the user preference changes and model the user long-term and short-term preferences.…”
Section: User Preferences Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several news recommendation methods based on deep learning techniques are proposed (Okura et al 2017;Khattar et al 2018;Wang et al 2018;Wu et al 2019c;An et al 2019;Wu et al 2019a, d, e;Ge et al 2020;Hu et al 2020). For example, Okura et al (2017) proposed to learn representations of users from the representations of their browsed news using a GRU network.…”
Section: Related Workmentioning
confidence: 99%